A New Therapeutic Approach for Brain Delivery of Epigallocatechin Gallate: Development and Characterization Studies - Kaur, Harjeet; Kumar, Baldeep; Chakrabarti, Amitava; Medhi, Bikash; Modi, Manish; Radotra, Bishan D.; Aggarwal, Ritu; Sinha, Vivek Ranjan (Current Drug Delivery, 2019)
Background: Blood-brain permeability is the primary concern when dealing with the biodistribution of drugs to the brain in neurological diseases. Objective: The purpose of the study is to develop the nanoformulation of Epigallocatechin gallate (EGCG) in order to improve its bioavailability and penetration into the brain. Methods: EGCG loaded Solid Lipid Nanoparticles (SLNs) have been developed using microemulsification method and pharmacological assessments were performed. Results: Surface morphology and micromeritics analysis showed the successful development of EGCG loaded solid lipid nanoparticles with an average size of 162.4 nm and spherical in shape. In vitro release studies indicated a consistent and slow drug release. Pharmacological evaluation of SLN-EGCG demonstrated a significant improvement in cerebral ischemia-induced memory impairment. Conclusion: The results indicate that the EGCG loaded SLNs provide a potential drug delivery system for improved delivery of EGCG to the brain, hence, enhancing its brain bioavailability.
Keywords: memory